2023
DOI: 10.1093/eurpub/ckad059
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in heart failure care in four European countries: a comparative study

Bianca Steiner,
Anne Neumann,
Yannick Pelz
et al.

Abstract: Background In Europe, more than 15 million people live with heart failure (HF). It imposes an enormous social, organizational and economic burden. As a reaction to impending impact on healthcare provision, different country-specific structures for HF-care have been established. The aim of this report is to provide an overview and compare the HF-care approaches of Germany, Ireland, the Netherlands and the UK, and to open the possibility of learning from each other’s experience. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Despite patients’ initial reluctance to embrace these changes, recent studies found many patients with HF and their caregivers recognise the benefits of the modern digital and artificial intelligence (AI) era. [ 11 , 12 ]…”
mentioning
confidence: 99%
“…Despite patients’ initial reluctance to embrace these changes, recent studies found many patients with HF and their caregivers recognise the benefits of the modern digital and artificial intelligence (AI) era. [ 11 , 12 ]…”
mentioning
confidence: 99%